Resistance model for confined circular reinforced concrete columns under eccentric loads - Marta Lutomirska; Aleksander Szwed; Aneta Krystyna Łuszczynska; Tomasz Andrzej Lutomirski (Archives of Civil Engineering)
Circular reinforced concrete columns with spiral reinforcement exhibit an increased ductility and resistance due to the confinement effect. Many experimental investigations and theoretical studies related to this topic are focused on columns under axial load, while those for eccentric load are seldom. The scope of the paper is to present a developed calculation model of resistance for eccentrically loaded confined circular concrete columns. The model assumptions extend procedures of the ACI and Eurocode to the confined concrete case. In order to determine the resistance of columns in the form of the force-moment interaction diagrams, a special procedure is elaborated and described in detail. The peak stress and corresponding strain for axially loaded confined concrete is calculated using the Richart’s model. Then, an increase of ultimate strength capacity due to confinement is related to the axial strain level. The more the eccentricity, the less the confinement effect is engaged in the column resistance. The contribution of spiral reinforcement in the bearing capacity is the greatest in concentrically loaded columns and it vanishes at the point where axial strain in the concrete column is equal to zero, which initially governed the beneficial effect of the spiral reinforcement. A sample interaction diagram is obtained for the selected design case and compared with the diagram for unconfined column.